Accessory Hepatic Lobe in Right Lumber – An Incidental Finding - Shrestha, M K; Ghartimagar, D; Ghosh, A (Journal of Nepal Health Research Council, 2015)
An accessory lobe of liver is a rare congenital anomaly which can be detected incidentally or can even present as acute surgical emergency due to torsion. We report a case of accessory hepatic lobe in right lumbar region in a 21years old female who came for a ultrasound abdomen for lower abdominal pain. We report the importance of ultrasonography and Computed Tomogram (CT) scan for the diagnosis of accessory hepatic lobe. Â Keywords: Â accessory hepatic lobe; liver; CT scan.